Application of Advanced Statistical Techniques for Horticultural Crops Research: Present Status and Future Prospects - R Venugopalan (Journal of the Indian Society of Agricultural Statistics, 2026)
Statistical methods play a vital role in different areas of horticultural crops research right from planning of any research experiment till selection of appropriate tool for data analysis to unravel many of the hidden results. They are central to horticultural research, enabling robust analysis of complex research issues entailing multi-disciplinary fields such as crop improvement, production, protection, post-harvest management, climate resilience, and socio-economic studies. The present communication, while delineating several of such multidisciplinary research outcomes, it also provides a road map for its potential application in emerging areas of research. Further, detailed descriptions of the statistical methodologies employed are referenced to the original sources for readers seeking methodological specifics.